PELAKSANAAN HAK KLIEN PEMASYARAKATAN UNTUK MEMPEROLEH BIMBINGAN DI BALAI PEMASYARAKATAN KLAS I PADANG - Rahman, Retno (Universitas Ekasakti, 2021)
One of the goals of the Correctional System is to prepare Correctional Inmates (WBP) or hereinafter referred to as Correctional Clients so that they can integrate in a healthy manner and play a responsible role again in the family and the wider community. Class I Correctional Center Padang as a Technical Implementation Unit from the Ministry of Law and Human Rights of West Sumatra as a law enforcer who carries out duties in the field of guiding Correctional Clients who must carry out correctional duties and functions based on applicable legal rules so that the fulfillment and protection of Human Rights can be realized. The fulfillment of the client's rights is regulated in the Law of the Republic of Indonesia Number 12 of 1995 concerning Corrections and the rules for its implementation.